Service interactions modeling for improved management of public transport systems. (March 2016) - Dragoicea, Monica; Borangiu, Theodor; Voinescu, Iulia
This paper shows how service science principles may be used for engineering and realizing improved public transport services. It approaches a value co-creation perspective for the management of public transport service operations based on an activity-based model of a generic service system that allows capturing requirements for software intensive service systems. The main focus is on specific implementation issues of the activity-based model of the generic service system, with a strong accent on its most representative component, the service set-up and configuring unit. This model is applied in a case study for planning of a public transport service and describes how a specific service reconfiguring request is formulated. This examination is further used as a document of requirements that drives the construction of an agent-based model expressing value-creation interactions among service system's stakeholders in public transport services. The usefulness of the developed agent-based model for the analysis of service systems operational capabilities is suggested through simulation. A business scenario related to the management of public transport services is described, and the defined agent-based model is executed with the Presage2 multi-agent programming platform in order to capture specific issues of piece-of-work planning. The proposed approach, evaluated on the simple working scenario, fosters the role of service interaction modeling in supporting a public transport service system to dynamically adapt its operational capabilities in delivering good public transport services, as more or less quantifiable changes can affect service delivery over time.